2020
DOI: 10.1155/2020/6230784
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Combining Ability for Early Maturity and Yield in Rice (Genus: Oryza) at the Kenyan Coast

Abstract: The main challenges facing rain-fed rice farming in Kilifi County at the Kenyan coast are inadequate and erratic rainfall, inadequate skills, and poorly developed infrastructure. Of great importance is erratic rainfall that tends to depress towards the end of long rain season, leading to crop failure. Combining ability analysis is one of the most valuable tools used to ascertain gene action effects and help in selecting desirable parents for making crosses and coming up with high yielding and early maturing li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Variety-testers Saule, Donetskiy 8, have a fairly low GCA in height, but in the course of further analysis of the combining ability, their negative impact on all traits of productivity have been revealed. However, as studies by Al-Imran Dianga [14] have shown, the results of one population cannot be extrapolated to another population. The effect of the gene must be assessed for each population, that is, the values of the specific combining ability must be assessed and taken into account.…”
Section: Plant Heightmentioning
confidence: 97%
See 1 more Smart Citation
“…Variety-testers Saule, Donetskiy 8, have a fairly low GCA in height, but in the course of further analysis of the combining ability, their negative impact on all traits of productivity have been revealed. However, as studies by Al-Imran Dianga [14] have shown, the results of one population cannot be extrapolated to another population. The effect of the gene must be assessed for each population, that is, the values of the specific combining ability must be assessed and taken into account.…”
Section: Plant Heightmentioning
confidence: 97%
“…Literature review has shown that different genes are involved in the determination of traits, sometimes they have a contradictory character in the limit of one agricultural crop, which, apparently, depends on the genotype of the parental lines involved in hybridization and, in the case of polygenic inheritance, can be also determined by the growth conditions of plants [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Cultivar-testers, Saule and Donetskiy-8, have a fairly low GCA in height, but in the course of further analysis of the combining ability, their negative impact on the productivity traits has been recorded. However, according to Dianga et al (2020), the results of one population cannot be extrapolated to another, and the effects of the various genes must be assessed for each population, taking into account assessing the specific combining ability.…”
Section: Plant Heightmentioning
confidence: 99%
“…Rice yield per hectare increased from 5.7 t ha −1 in the 1980s to 9.52 t ha −1 in the 2000s as a result of the widespread adoption of semi-dwarf and early maturing Egyptian cultivars. However, the rice production could not keep up with the growing population and diminishing water resources (Dianga et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The general combining ability (GCA) indicates an additive gene action and measures the average performance of parental lines. The specific combining ability (SCA) represents a non-additive gene action associated with dominance, overdominance, and epistatic effects and quantifies the performance of hybrid combinations (Dianga et al, 2020).…”
Section: Introductionmentioning
confidence: 99%